A rare case of drug sensitive adult‐onset temporal lobe epilepsy due to a focal cortical dysplasia revealed by ictal coughing: First report in sub‐Saharan Africa. Issue 3 (27th March 2023) - Chokote, Eric‐Samuel; Ngarka, Leonard; Takoeta, Emmanuel Oben; Kengni, Hermann Nestor Tsague; Nfor, Leonard N.; Mengnjo, Michel K.; Mendo, Edwige Laure; Djeutcheu, Fabrice; Yepnjio, Faustin N.; Tatah, Godwin Y.; Mbassi, Hubert Désiré Awa; Njamnshi, Alfred K.
Abstract: This case suggests that clinicians should consider seizures as a differential diagnosis of paroxystic cough with loss of consciousness. Focal cortical dysplasia should equally be screened for with magnetic resonance imaging (MRI) scans even in adults with epilepsy in sub‐Saharan Africa. Abstract : This case suggests that clinicians should consider seizures as a differential diagnosis of paroxystic cough with loss of consciousness. Focal cortical dysplasia should equally be screened for with Magnetic Resonance Imaging (MRI) scans even in adults with epilepsy in sub‐Saharan Africa.